Astragalin Inhibits the Proliferation and Migration of Human Colon Cancer HCT116 Cells by Regulating the NF-κB Signaling Pathway - Yang, Min; Li, Wen-Yun; Xie, Jing; Wang, Zi-Lin; Wen, Yan-Long; Zhao, Cun-Chao; Tao, Liang; Li, Ling-Fei; Tian, Yang; Sheng, Jun (Frontiers in Pharmacology, 2021)
Astragalin is a flavonoid found in a variety of natural plants. It has anti-inflammatory, anti-oxidant effects and has inhibited effects against several malignant tumor cell types. However, its effects on colon cancer and the molecular mechanisms have remained to be elucidated. In this study, we evaluated the inhibitory effect of astragalin on proliferation and migration of human colon cancer HCT116 cells in vitro and in vivo. Furthermore, we elucidated the mechanism of these effects. The results showed that astragalin significantly inhibited the proliferation and diffusion of HCT116 cells by induced apoptosis (by modulation of Bax, Bcl-2, P53, caspase-3, caspase 6, caspase 7, caspase 8, caspase 9 protein express) and cell cycle arrest (by modulation of Cyclin D1, Cyclin E, P21, P27, CDK2, CDK4 protein express). Moreover, astragalin suppressed HCT116 cell migration by inhibiting the expression of matrix metalloproteinases (MMP-2, MMP-9). In addition, astragalin significantly downregulated the expression of key proteins in the NF-κB signaling pathway and inhibited the transcriptional activity of NF-κB P65 stimulated with inflammatory cytokines TNF-α, thereby inhibiting the growth of colon cancer cells in vitro. Our further investigations unveiled astragalin gavage significantly reduced the proliferation of colon cancer xenograft in nude mice, in vivo experiments showed that tumor growth was related to decreased expression of apoptotic proteins in tumor tissues and decreased activity of the NF-κB signaling pathway. In summary, our results indicated that astragalin inhibits the proliferation and growth of colon cancer cells in vivo and in vitro via the NF-κB pathway. Therefore, astragalin maybe become a potential plant-derived antitumor drug for colon cancer.